Struktur Komunitas Ikan Karang di Perairan Kota Sorong, Papua Barat Daya, Indonesia - Ghofir, Abdul; Haryanti, Dwi; Hartati, Retno; Orisu, Anthon Apolos (Universitas Diponegoro, 2025)
Reef fish are one of the biota that are sensitive to environmental changes. Their abundance and diversity are supported by good coral reef conditions. This makes them a bioindicator of coral reef conditions. This study aims to examine the diversity of reef fish, ecological indices, and conditions of coral reef benthic substrates in Sorong City waters from September to November 2024 at ten research stations using the Underwater Visual Census (UVC) and Underwater Photo Transect (UPT) methods. The study found 174 species of reef fish from 26 families (107 major, 55 target, and 12 indicator). The diversity (H') and evenness (E) indices were moderate to high at 1.59-3.41 and 0.41-0.89, respectively, and dominance (C) was low at 0.04-0.48. PCA analysis showed that hard coral cover (HC) as the main determinant of reef fish community structure correlated with the families Pomacentridae, Chaetodontidae, Scaridae, Pempheridae, and Blennidae. This finding is important for marine resource management and conservation in the waters of Sorong City. Ikan karang merupakan salah satu biota yang peka dengan perubahan lingkungan. Kelimpahan dan keanekaragamannya didukung oleh kondisi terumbu karang yang baik. Hal ini menjadikannya sebagai bioindikator kondisi terumbu karang. Penelitian ini bertujuan mengkaji keanekaragaman ikan karang, indeks ekologi, dan kondisi substrat bentik terumbu karang di perairan Kota Sorong pada September-November 2024 di sepuluh stasiun penelitian menggunakan metode Underwater Visual Census (UVC) dan Underwater Photo Transect (UPT). Hasil penelitian ditemukan ikan karang 174 spesies dari 26 famili (107 mayor, 55 target, dan 12 indikator). Indeks keanekaragaman (H’) dan keseragaman (E) sedang hingga tinggi 1,59-3,41 dan 0,41-0,89, serta dominasi (C) rendah 0,04-0,48. Analisis PCA menunjukkan tutupan karang keras (HC) sebagai penentu utama struktur komunitas ikan karang berkorelasi dengan Pomacentridae, Chaetodontidae, Scaridae, Pempheridae dan Blennidae. Temuan ini penting untuk pengelolaan sumber daya laut dan konservasi di perairan Kota Sorong.